Inocybe cervenianensis (Agaricales, Inocybaceae), a new species in the I. flavoalbida clade from Italy - Dovana, Francesco; Bizio, Enrico; Garbelotto, Matteo; Ferisin, Giuliano (Phytotaxa, 2021)
The authors describe the macro- and microscopic features of Inocybe cervenianensis, a new taxon belonging to the genus Inocybe sensu stricto. The description is illustrated with photographs of the basidiomes in their natural habitat and photographs of the main microscopic features. Molecular data (nrITS and RPB2) support the recognition of this new species.